Effects of Changes in Background Colour on the Identification of Own- and Other-Race Faces. (April 2019) - Havard, Catriona; Richter, Stephanie; Thirkettle, Martin
The current study investigated whether small differences in the background colours between the lineup members would influence identification accuracy of own-race and other-race faces. Using the well-established 1-in-10 paradigm, half of the array faces had exactly the same backgrounds, and half were on backgrounds of slightly different hues of green. For target present arrays, participants were more accurate at identifying own-race faces when compared with the other-race faces when all backgrounds were the same. However, when backgrounds had slightly different hues, there was no difference in how accurate people were at identifying faces from both races. For target absent arrays, participants were more likely to incorrectly choose a face if the backgrounds were not all the same, regardless of the race of faces. Real-world implications from these findings are that using lineups where the backgrounds are slightly different hues may increase the likelihood of the false identification of innocent suspects.